(untitled) (Research, Society and Development, 2020)
The aim of this study was to verify and compare vocal, respiratory and transverse abdominal muscle activation measurements before and after a physiotherapeutic protocol for intensive training of the body force center musculature in a voice professional. A 21-year-old female journalist with no vocal complaint participated. Original, retrospective case report, approved by the Research Ethics Committee (nº 40680614.7.0000.5346). It was collected: sustained emission of /a/, /i/, /u/, /s/, /z/, /e/ and the counting of numbers in usual pitch and loudness, of /e/ voiceless, of Modal Sound Pressure, dynamic and sung extension, maximal respiratory pressures, forced vital capacity and transverse abdomen activation, by means of a sphygmomanometer with a pressure biofeedback unit. Afterwards, a physiotherapeutic protocol for intensive training of the body force center and reevaluation was applied. Emissions support, modal and minimum Sound Pressure Level, sung extension, maximal respiratory pressures and activation of the transverse abdomen increased; and there was a reduction in the maximum Sound Pressure Level and the difference between the vowel average and the number count. Thus, intensive physical therapy training at the body strength center improved respiratory control and pneumophonoarticulatory coordination.